Walks in the Quarter Plane with Multiple Steps - Kauers, Manuel; Yatchak, Rika (Discrete mathematics and theoretical computer science, 2015)
We extend the classification of nearest neighbour walks in the quarter plane to models in which multiplicities are attached to each direction in the step set. Our study leads to a small number of infinite families that completely characterize all the models whose associated group is D4, D6, or D8. These families cover all the models with multiplicites 0, 1, 2, or 3, which were experimentally found to be D-finite — with three noteworthy exceptions. Nous étendons la classification des marches aux plus proches voisins dans le quart de plan à des modèles dans lesquels une multiplicité est attachée à chaque direction de l’ensemble des pas. Notre étude identifie un petit nombre de familles infinies qui caractérisent complétement tous les modèles dont le groupe est D4, D6 ou D8. Ces familles contiennent tous les modèles à multiplicités 0, 1, 2 ou 3 dont il a été prouvé expérimentalement qu’ils étaientD-finis —avec trois exceptions notables.